2020
DOI: 10.1002/ejic.202000364
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated Amino‐Acid‐Based Ionic Liquids for CO2 Capture

Abstract: Ionic liquids have gathered special attention due to their potential for carbon dioxide capture, and their potential as solvents for mitigation of climate change. Following the scope of previous works, amino‐acid‐based ionic liquids encapsulated (ENILs) into carbonaceous submicrocapsules are here proposed as a novel material for CO2 capture. The ENILs prepared using tetrabutylphosphonium acetate ([P4,4,4,4][Ac]), used as reference, (2‐hydroxyethyl)trimethylammonium l‐phenylalaninate ([N1,1,1,2(OH)][L‐Phe]), (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Fatty acid ionic liquids were used successfully in various industries for different purposes, such as pharmaceutical [ 136 ], biorefining processes [ 137 ], solvents and co-solvents [ 138 , 139 , 140 ], dissolution and levulination of cellulose [ 141 ], formation of aqueous biphasic systems [ 142 ], CO 2 capture [ 143 , 144 ], catalyst [ 145 ], lubricant additives [ 146 ], plant protection products [ 147 ], and extraction agents [ 148 ]. Therefore, the demulsification potential of bio-based ionic liquids, as well as their human health effects, are worthy of further investigations in future.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Fatty acid ionic liquids were used successfully in various industries for different purposes, such as pharmaceutical [ 136 ], biorefining processes [ 137 ], solvents and co-solvents [ 138 , 139 , 140 ], dissolution and levulination of cellulose [ 141 ], formation of aqueous biphasic systems [ 142 ], CO 2 capture [ 143 , 144 ], catalyst [ 145 ], lubricant additives [ 146 ], plant protection products [ 147 ], and extraction agents [ 148 ]. Therefore, the demulsification potential of bio-based ionic liquids, as well as their human health effects, are worthy of further investigations in future.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…However, the most practical one is CO 2 capture from concentrated sources such as power plants and natural gas production. These capturing agents include physical and chemical sorption/stripping technologies with either alkanolamines [5][6][7][8] or ionic liquids, [9][10][11][12][13] carbonaceous materials, 14 zeolites 15 or metal-organic frameworks, [16][17][18] and amine-impregnated/-grafted solid supports. 19 However, the latter materials have been reported to have low thermal stability in the desorption cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Further, 13 C CP-MAS NMR spectroscopy (Fig. 3) was carried out to confirm the presence of carbamates under the applied conditions.…”
mentioning
confidence: 99%
“…For an efficient carbon capture, a large number of studies have focused on how to design functionalized ILs. , In 2002, Davis et al reported for the first time that amino-containing ILs performed well in the CO 2 absorption. After that, a number of amino-functionalized ILs were prepared and used for CO 2 capture and transformation. As natural amino resources, amino acids are abundant in nature and possess many excellent properties, and have been used as anion or cation in the preparation of new ILs. It is found that these amino acid ILs, as one class of the amino-functionalized ILs, have high CO 2 absorption capacity and great potential in practical CO 2 absorption. For example, the CO 2 absorption capacity by the ILs with iminodiacetic acid (IDA) anions could be as high as 1.69 mol CO 2 mol –1 IL …”
Section: Introductionmentioning
confidence: 99%